Research data management and openness: The role of data sharing in developing institutional policies and practices. Issue 4 (1st September 2015) - Higman, Rosie; Pinfield, Stephen
Abstract : Purpose: – The purpose of this paper is to investigate the relationship between research data management (RDM) and data sharing in the formulation of RDM policies and development of practices in Higher Education Institutions (HEIs). Design/methodology/approach: – Two strands of work were undertaken sequentially: first, content analysis of 37 RDM policies from UK HEIs; and second, two detailed case studies of institutions with different approaches to RDM based on semi-structured interviews with staff involved in the development of RDM policy and services. The data are interpreted using insights from Actor Network Theory. Findings: – RDM policy formation and service development has created a complex set of networks within and beyond institutions involving different professional groups with widely varying priorities shaping activities. Data sharing is considered an important activity in the policies and services of HEIs studied, but its prominence can in most cases be attributed to the positions adopted by large research funders. Research limitations/implications: – The case studies, as research based on qualitative data, cannot be assumed to be universally applicable but do illustrate a variety of issues and challenges experienced more generally, particularly in the UK. Practical implications: – The research may help to inform development of policy and practice in RDM in HEIs and funder organisations. Originality/value: – This paper makes an early contribution to the RDM literature on the specific topic of the relationship between RDM policy and services, and openness – a topic which to date has received limited attention.